HUBUNGAN INDEKS MASSA TUBUH, DURASI LATIHAN DAN VO2MAX PADA PEMAIN SEPAK BOLA AMATIR USIA 11-14 TAHUN DI SEKOLAH SEPAK BOLA TAHUN 2022 - Rovika Trioclarise; Ganesa P.D Kurniawan; Intan Sukma Anggreani (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Background: Body Mass Index (BMI) has a negative relationship with a fitness level which means the higher the BMI value, the lower the body fitness test score. A person's fitness can be viewed from aerobic capacity on cardiorespiratory endurance and physical exercise. Effective physical exercise is endurance and includes a certain duration, frequency and intensity. Methods: This research is a “cross sectional” which is done once at a time to find the relationship between Body Mass Index, exercise duration and Vo2Max in soccer players amateurs aged 11-14 years in soccer schools located in Jakarta and Depok. Results: hypothesis testing was carried out using the Spearman test with the results for body mass index with VO2Max of -0.218 for the relationship between body mass index and duration of exercise there was a correlation coefficient of 0.346, and while the relationship between VO2Max and duration of exercise there was a correlation coefficient of 0.269.Conclusion: There is a relationship between body mass index and duration of exercise on VO2Max in amateur soccer players aged 11-14 years at the Football School in 2022.